A highly selective ratiometric fluorescent probe for biothiol and imaging in live cells. Issue 49 (3rd May 2016) - Gao, Baozhen; Cui, Lixia; Pan, Yong; Zhang, Guomei; Zhou, Ying; Zhang, Caihong; Shuang, Shaomin; Dong, Chuan
Abstract : A new N -butyl-4-amino-1, 8-naphthalimide-based colorimetric and ratiometric fluorescent probe for the detection of biothiols (cysteine, homocysteine, and glutathione) was designed and synthesized. Abstract : A new N -butyl-4-amino-1, 8-naphthalimide-based colorimetric and ratiometric fluorescent probe for the detection of biothiols (cysteine, homocysteine, and glutathione) was designed and synthesized. The probe exhibited good selectivity and sensitivity toward biothiols over other non-thiol-bearing amino acids and common anions with significant changes in both color (from colorless to yellow) and fluorescence (from blue to yellow-green). The mechanism is based on cleavage of disulfide by thiols followed by an intramolecular cyclization to give the product, N -butyl-4-amino-1, 8-naphthalimide, which showed outstanding intramolecular charge transfer (ICT). Therefore, ratiometric fluorescence signal was observed. Furthermore, the probes were successfully applied for visualizing endogenous thiols in living cells.